2003
DOI: 10.1088/0029-5515/43/11/018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reflections on the operation of the 2 MW, CW 170 GHz coaxial cavity gyrotron for ITER

Abstract: The influence of reflections on the operation of the 2 MW, CW 170 GHz coaxial cavity gyrotron oscillating in the TE − 34,19 mode is studied. In particular, frequency-independent power reflections, e.g. from plasma or some elements of the transmission line, larger than 1% and occurring in a poor phase may lead to oscillation breakdown and should be avoided. Frequency-dependent reflections from a specially designed diamond window influence mode competition, but contract the oscillation region of the operating mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It has been shown that the specific mode competition scenarios for ITER coaxial gyrotron published earlier in Ref. 5 are correct in spite of the fact that an oversimplified reflection model has been used in that paper. It is also shown that possible reflections of the operating and parasitic modes should not change significantly the start-up scenario for the ITER gyrotron with optimal parameters.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…It has been shown that the specific mode competition scenarios for ITER coaxial gyrotron published earlier in Ref. 5 are correct in spite of the fact that an oversimplified reflection model has been used in that paper. It is also shown that possible reflections of the operating and parasitic modes should not change significantly the start-up scenario for the ITER gyrotron with optimal parameters.…”
Section: Discussionmentioning
confidence: 82%
“…The analysis of Eq. (5) shows that, as the reflection parameter increases, this solution for the intensity of the second mode increases starting from zero, while simultaneously the intensity of the first (original) mode M 1 Ј= M 1 / decreases starting from M 1 Ј=1 for = 0. This solution merges with another solution and they disappear when the reflection parameter reaches its critical value = cr = ͑59/ 64͒͑−1 + ͱ 1 + 512/ 3481͒Ӎ0.0655.…”
Section: Qualitative Theory Of the Effect Of Reflectionsmentioning
confidence: 93%
See 2 more Smart Citations
“…On the other hand, many applications in physics, industry, and even medicine would take advantage of the bandwidth broadening resulting from chaotic oscillations: e.g., significantly better uniformity of volumetric microwave heating can be achieved using waves with a broadband spectrum. Although stationarity of microwave oscillations seems to be characteristic for highefficiency operation of an ideal (reflectionless) tube [4], it has been found that reflection of microwaves from the window, the load, or output-section inhomogeneities could lower the threshold for stochastic oscillations even to one tenth of its unperturbed value [6], [7], negatively influence mode competition [8], [9], and give rise to frequency jumps during pulses which heat the cavity [10]. Recently it has been suggested on the basis of numerical simulations [11], [12] that reflections make a gyrotron show complicated quasiperiodic behavior rather than oscillate chaotically.…”
mentioning
confidence: 99%